Simulation and characterization of aluminium-based metal matrix composite - Sulaiman, Suraya (2011)
This research work is concerned with the areas of computer simulation of casting process to investigate the mould filling and solidification characteristics of aluminium-11.8% silicon alloy matrix (LM6 alloy matrix) reinforced at five different weight percentages; 0%, 5%, 10%, 15%, and 20% of titanium carbide (TiC) as particulates. The experimental worksfocused on the cooling curve, microstructural and mechanical properties of composite material. Effects on different weight percentages (wt%) addition of the TiC particulates distribution in LM6 alloy matrix are studied. The simulation software used is AnyCasting. The temperature and time during solidification process for experimental work and simulation are compared.The cylinder composite castinghas been made by pouring the composite mixture in sand and copper permanent metallic moulds. The tensile specimens were then preparedin accordance to ASTM B557 M-94 specifications, hardness specimens were tested using MITUTOYO ATK-600 MODEL machine and microstructure of the fracture surface have done by using Scanning Electron Microscopy (SEM).The outcome of the investigations reveals that the tensile strength and hardness are enhanced from 0wt% to 10wt% of TiCand start to decrease after addition of 10wt%.ofTiC.Good bonding and wettability between the composites ranging from 0%wt. to 10%wt. of TiC influence the close distribution of TiC particles in the LM6 alloy matrix. The addition of 10%wt. to 20%wt. of TiC in LM6 alloy matrix cause the lower resistance and load-bearing capacity and the particle are no longer isolated with the LM6 alloy matrix causing the worse value of tensile strength and hardness.